Phase 2 study of the bispecific T-cell engager (BiTE) antibody blinatumomab in relapsed/refractory diffuse large B-cell lymphoma - Viardot, Andreas; Nagorsen, Dirk (Blood, 2016)
Few patients with relapsed/refractory diffuse large B-cell lymphoma (DLBCL) achieve prolonged disease-free survival. Blinatumomab, a bispecific T-cell engaging antibody construct, transiently links CD3-positive T cells to CD19-positive B cells. This phase 2 study evaluated stepwise (9-28-112 μg/d with weekly dose increases; n = 23) or flat (112 μg/d; n = 2) dosing of blinatumomab by continuous infusion, with dexamethasone prophylaxis, in patients with relapsed/refractory DLBCL. Patients received a median of 3 prior lines of therapy. Median time since last regimen was 1.5 months. Seventeen patients ended treatment in cycle 1 (induction), 7 in cycle 2 (consolidation), and 1 in retreatment. Among 21 evaluable patients, the overall response rate after 1 blinatumomab cycle was 43%, including complete responses (CRs) in 19%. Three patients had late CR in follow-up without other treatment. The most common adverse events with stepwise dosing were tremor (48%), pyrexia (44%), fatigue (26%), and edema (26%). Grade 3 neurologic events with stepwise dosing were encephalopathy and aphasia (each 9%) and tremor, speech disorder, dizziness, somnolence, and disorientation (each 4%). Of 5 (22%) patients who discontinued stepwise dosing because of adverse events, 4 (17%) had neurologic events. Most neurologic events resolved. The flat-dose cohort was stopped because of grade 3 neurologic events in both patients. Blinatumomab monotherapy appears effective in patients with relapsed/refractory DLBCL, a heavily pretreated patient population with a high unmet medical need. Further studies need to define the optimal approach to achieve the target dose without early dropout.